An Electrochemical Sensor Based on Nitrogen‐doped Carbon Nanofiber for Bisphenol A Determination. Issue 3 (14th August 2015) - Sun, Jinying; Liu, Yang; Lv, Simin; Huang, Zhirong; Cui, Liao; Wu, Tie
Abstract: In this paper, bisphenol A was determined by electrochemical method at a nitrogen‐doped carbon nanofiber modified carbon paste electrode (NCNF/CPE) with high sensitivity and good selectivity. NCNF was obtained by a simple electrospinning followed by carbonization procedure, in which polyacrylonitrile (PAN) as precursor and nitrogen doping was realized by re‐utilizing the tail gas that produced in the thermal pretreatment process. Good reproducibility and high stability were obtained for BPA detection at NCNF modified CPE. Current response plotted with BPA concentration was linear in the range of 0.1–60 μM with LOD of 0.05 μM. The proposed electrochemical sensor was employed for BPA determination with satisfactory recoveries for real water samples, indicating the practical applicability of NCNF/CPE. Abstract :